A experiência de criação de um curso através de software de autoração de multimídia: uma introdução - Gauthier, Fernando Álvaro Ostuni (1997)
The paper presents an introduction to multimedia technology and its evolution. Multimedia elements and tools are defined and multimedia authoring tools listed. A script for multimedia creation is suggested. The script was used during the development multimedia Software for a production management course. Some remarks about the project development are commented. Finally, the way in which the interactive Software can help in the user’s learning process is evaluated.